Thermal Conductivity: Understanding Thermal Insulation in Porous, Particulate Materials (Adv. Funct. Mater. 38/2017). (10th October 2017) - Ruckdeschel, Pia; Philipp, Alexandra; Retsch, Markus
Abstract : In article number1702256, Markus Retsch and co‐workers report how hollow silica sphere colloidal crystals provide a versatile and powerful way to control the nano‐ and mesostructure on several length scales. The highly‐ordered particle arrangement results in bright opalescent colors. The structural control of these ensembles is used to understand heat transport in porous materials.